Correlation between morphological characteristics and situational motor abilities of young female handball players - Bojic, I.; Kocic, M.; Velickovic, M.; Nikolic, D. (XX Scientific Conference.FIS COMMUNICATIONS 2017" in physical education, sport and recreation (Nis, Serbia, october 19-21st, 2017), 2017)
A morphological motor profile of a player has a vital role in achieving success in modern handball. The aim of this research was to establish the correlation between morphological characteristics and specific motor abilitie of female handball players at the age of 13 to 14. The sample was comprised of 30 examinees, female handball players from the school of handball of the female handball club "Naisa", Serbia. A set of 22 measuring instruments was applied for estimating and evaluating morphological characteristics, whereas a set of 8 tests was used for situational-motor abilities (Shooting from a 7meter distant high stand [n/4 shots], Shooting from an 8meterdistant step [n/4 shots], Jump shot from 9 meters [n/4 shots], Starting speed with the ball in a 20meter run [sec.], Throwing and catching the ball rebounded off the wall with onehand [n/30 sec.], Dribbling in "eights" [sec.], Dribbling along a 3meter long line of a square [sec.] and Players' movements with and without the ball with shooting on goal [sec.]). Canonical-correlation analysis was used for obtaining a high statistically significant canonical correlation (R=0,90; p=0,01) between the morphological characteristics (the body volume) and the situational and motor variables (shooting precision).